Trois sonates pour le piano-forte : Oeuv. 2 ..., No. 3 ... composées et dédiées à J. Haydn par L. van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; Jean Aug. Böhme; Hamburg, 2022)
Edition of the Piano Sonata no. 3 in C major, op. 2, no. 3, published in an unnamed series by Jean Aug. Böhme in Hamburg. With decorative passé-partout title page that lists individual and set prices for all three sonatas of op. 2. Paginated 28-43. Plate number 3.